Gonococcal Subcutaneous Abscess and Pyomyositis: A Case Report. (5th August 2012) - Jitmuang, Anupop; Boonyasiri, Adhiratha; Keurueangkul, Nukool; Leelaporn, Amornrut; Leelarasamee, Amorn
Abstract : Disseminated gonococcal infection (DGI) is an uncommon complication of Neisseria gonorrhoeae infection, its manifestation varies from a classic arthritis-dermatitis syndrome to uncommon pyogenic infections of several organs. Herein, we reported atypical presentation of DGI with subcutaneous abscess of right knee, pyomyositis of right lower extremity, and subsequently complicated by Escherichia coli pyomyositis. This infection responded to appropriate antimicrobial therapy and prompt surgical management with good clinical outcome.